Status of Pass-out B.Sc. Nursing Graduates from BP Koirala Institute of Health Sciences Dharan Nepal - Mehata, Ram Sharan; Shrestha, Erina (Journal of Nursing Education of Nepal, 2022)
Introduction: Job satisfaction is a critical issue for any institute and administration. The objectives of the study were to find out the status of pass-out B.Sc. Nursing graduates. Methods: Descriptive cross-sectional study design was adopted among the pass-out B.Sc. nursing graduates of BPKIHS from 1996-2015 batches after obtaining ethical clearance from IRC, BPKIHS. Using convenient sampling technique total 107 subjects were included in the study. Pre-tested questionnaire was used to collect data by using Google Drive Online Form. The data was analyzed using SPSS Version-16. Nearly half (45.8%) of the subjects were 31-35 years, married (59.52%), and completed M.Sc. Nursing degree (33.48%). It was found that most of the subjects were satisfied with job. There is significant association between age group with professional status (p=0.001), income (p=0.002), job-satisfaction (p=0.014); similarly, with work place (Nepal and abroad) and professional status (p=0.001), income (p=0.025), and job- satisfaction (p=0.001) are significantly associated. Conclusion: Based on the findings it is concluded that most of the pass-out graduates were satisfied with their job. Work places of subjects were significantly associated with nursing status, income, service provided, nursing image and job-satisfaction. Keywords: Status, Pass-out, Nursing, Students, Nepal